Cryopreservation Effect on Functional Characteristics of Thyroid Glandâ€™s Organ Cultures of Rabbits and Newborn Pig - Volkova, N. A.; Alabedalkarim, N. M.; Bozhok, G. A.; Bondarenko, T. P. (Problems of Cryobiology and Cryomedicine, 2006)
Biochemical and morphological properties of native and cryopreserved organ cultures of thyroid gland of rabbits (OCThGR) and newborn piglets (OCThGNP) were investigated. The OCThGR cells wereÂ  shown to be more sensitive to the effect of low temperature preservation. It was established, that the OCThGNP kept the capability to reparative processes after cryopreservation.